Effects of Planting Time and Cultivar on Leaf Physiology and Seed Yield of Soybean (Glycine max. (L.) Merr) - Eko Srihartanto; Didik Indradewa (Caraka Tani: Journal of Sustainable Agriculture, 2019)
The use of adaptive soybean cultivars with appropriate planting time on dry land can enhance the improvement of soybean growth and yield. This study aimed to determine changes in leaf physiological character and soybean yield as affected by different planting time and superior soybean cultivars. The experiment was conducted on the dry land of Inceptisol in Gunungkidul from November 2018 to March 2019. The experiment was arranged in a Split Plot Design with the main plot arranged in a Randomized Complete Block Design (RCBD) with three (3) replications. The main plots consisted of three planting times, i.e. early planting time–Pranoto Mongso, midldle planting time–Farmer Method and late planting–Katam Terpadu. The subplots consisted of four soybean cultivars, namely Anjasmoro, Argomulyo, Grobogan and Dega-1. The fertilizers used were organic fertilizer (2 t ha-1), Urea (50 kg ha-1) and KCl (50 kg ha-1). The results showed that the treatment of planting time and cultivar could increase leaf physiological activity, particularly the number of leaves, total leaf area, leaf area index and plant growth rate. Early planting time–Pranoto Mongso and middle planting time–Farmers Method produced higher plant dry weight (20.11 g; 24.21 g) and seed yields per plant (29.11 g; 26.75 g) than late planting (Katam Terpadu) did (20.30 g). Meanwhile, cultivar Dega-1 had higher seed yields per plant (30.11 g) than cultivar Grobogan (28.39 g), Argomulyo (23.35 g) and Anjasmoro (19.79 g) did.